PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING BERBANTU MEDIA POWER POINT TERHADAP HASIL BELAJAR SISWA - Ella Okfita Sari; Jumriana Rahayu Ningsih; Dwi Putri Musdansi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
The purpose of this study was to find out which student learning outcomes were better between using snowball throwing cooperative learning models assisted by power point media or using conventional learning models on hydrocarbon compound material in class XI MIPA SMA Negeri 1 Benai. The type of research used is a quasi experimental design with a posttest only group design. The sampling technique is cluster random sampling through drawing. Then it was found that the sample of class XI MIPA 4 studentas an experimental class and class XI MIPA 5 as a control class. The trial instrument used was content validity that was judged by 3 experts, item analysis (level of difficulty, differentiation, deseption effectiveness) and reliability of the questions processed by the help of ANATES. The test used was an objective written test of 20 questions. To test thenormality of the data used the Kolmogorov Smirnov test, the homogeneity test uses the Statistical Levene test and the hypothesis test uses the “t” test, namely the independent sample t test. The research hypothesis test showed that the value of sig. (1-tailed) was 0,000 < 0,05 then H0 was rejected. So that it can be concluded that student learning outcomes using cooperative learning models snowball throwing type assisted by power point media are better than student learning outcomes using conventional learning models.